Temperature and humidity control system for broiler chicken coops - Ramadiani Ramadiani; Eko Wiji Setio Budianto; Dharma Widada; Masayu Widiastuti; Muhammad Labib Jundillah (Institute of Advanced Engineering and Science, 2021)
Stress in chickens due to rising cage temperatures is a problem that is often faced by breeders, especially broiler breeders. Research with the title